Economic variables affecting spatial contrast for female forces In the government health sector in Baghdad Governorate for 2020 - Ahmed, Raad Mufeed; Allawi, Ibrahim Abd (Al-Adab Journal, 2022)
The research aims to identify the size of the female workforce working in the government health sector, and to reveal the economic variables affecting their distribution and spatial variance. In addition to the use of maps for the same purpose, the standard degree was adopted to clarify the variation of the economic variables affecting the phenomenon in question and to compare it visually with the size of the female workforce and at the level of administrative units. Using the Pearson correlation coefficient and multi-step regression, the research relied on the official publications of the Central Agency for Statistics and Information Technology, the data of the Ministry of Health and Environment and its health departments, and the field study for the year 2020. The research reached a set of results, the most important of which is the presence of spatial variation in the governorate of Baghdad and at the level of its administrative units in the ratios and rates of female health forces for the year 2019, as its size reached (40922) female workers, and the percentages varied according to the environment (urban and rural) and reached in urban (96.0%). And in the countryside (4.0%), it also varied spatially at the level of administrative units, as the Rusafa district center came with the highest percentage (22.1%), and it came with the lowest percentage in the viewing and Al-Abayji areas, and it amounted to (0.1%) for each, and the rest of the administrative units ranged in the proportions of the female workforce health between the above two ratios.